2021
DOI: 10.3390/children8050338
|View full text |Cite
|
Sign up to set email alerts
|

Educators Perspectives on the Value of Physical Education, Physical Activity and Fundamental Movement Skills for Early Years Foundation Stage Children in England

Abstract: There is a lack of information available for physical education (PE) provision in the early years foundation stage (EYFS), prompting concern about what is currently delivered in schools and the values behind the approaches taken. Using semi-structured interviews, this study investigated educators’ perspectives on the value of PE and physical activity (PA) for EYFS children across England in relation to opportunities for, barriers to, and benefits of PA and PE. This study collected important stakeholder views a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…Similar, to the points discussed above, in terms of the PA barriers, lack of staff training and confidence were one of the consistently reported barriers by the EYPs for PA promotion. Such observations align with the Dobell et al (2021) findings which highlights the need for the action to improve the quality of PA and FMS provision resources and training for EYPs.…”
Section: Supporting Pa and Eating Habitssupporting
confidence: 84%
See 3 more Smart Citations
“…Similar, to the points discussed above, in terms of the PA barriers, lack of staff training and confidence were one of the consistently reported barriers by the EYPs for PA promotion. Such observations align with the Dobell et al (2021) findings which highlights the need for the action to improve the quality of PA and FMS provision resources and training for EYPs.…”
Section: Supporting Pa and Eating Habitssupporting
confidence: 84%
“…Despite this, over 40% of the respondents had not heard of FMS before. These results are comparable to recent studies where primary school teachers demonstrated little to zero perceived comprehension on FMS, having any training on FMS (Eddy et al 2021) and thus, lack of confidence in its upskilling in children (Dobell et al 2021). Prior work by Ma et al (2021) using the Collective-Intelligence science approach with relevant stakeholders (e.g.…”
Section: Fms Perceptions and Practicessupporting
confidence: 81%
See 2 more Smart Citations
“…Per the Wisconsin Budget Project report (2017), school districts in Wisconsin faced extreme teacher shortages, with 46% of openings (1,153 jobs) including physical education teachers. Mousavi et al (2012) and Dobell et al (2021) suggests that PE is recognized as an important tool to ensure sufficient physical activity and that PE teachers play an important role in developing students' behaviors, attitudes, skills, and knowledge necessary to establish a lifelong physical activity. Given the enormous impact physical inactivity has in increased global morbidity, mortality, and health care costs, it is important to find strategies to maintain the quality of PE teaching by recruiting and retaining qualified K-12 Physical Education (PE) teachers in the United States (U.S.) Perhaps, understanding the factors associated with job satisfaction or dissatisfaction is one of keys to decrease the high attrition rate.…”
Section: Introductionmentioning
confidence: 99%